Rattus norvegicus ... - Don E. Wilson; Russell A. Mittermeier; Thomas E. Lacher, Jr (Lynx Edicions, 2017)
659. Brown Rat Rattus norvegicus French: Rat brun / German: \Wanderratte / Spanish: Rata parda Other common names: Common Rat, Domestic Rat, Fancy Rat, Lab Rat, Norway Rat, Sewer Rat Taxonomy. Mus norvegicus Berkenhout, 1769, “Great Britain.” Rattus norvegicus is currently in the R. nor- vegicus species group, along with R. nitidus and R. pyctoris, based on genetic and morphological data. There is less genetic and morphological variation in R.norvegicus than R. rattus, which was recently broken up into multiple species. Rattus norvegicus originated in south-western Siberia, northern China, and Japan and spread throughout Asia and Europe as early as the 16" century, although this is unconfirmed and the actual date when it became commensal with humansis uncertain. Since Western Civilization began colonizing the New World and Australia, R. norvegicus followed, spreading in similar ways as R. rattus, stowing away on ships. Subfossils of Brown Rats can be found all over the world and are indicators of when and ... : Published as part of Don E. Wilson, Russell A. Mittermeier & Thomas E. Lacher, Jr, 2017, Muridae, pp. 536-884 in Handbook of the Mammals of the World – Volume 7 Rodents II, Barcelona :Lynx Edicions on page 829, DOI: 10.5281/zenodo.6887260 ...